A Handbook on Multidisciplinary Approaches in Research (Volume 1) - Sandeep Bishla; Sahab Ram Kumawat (AG Volumes, 2023)
Accounting is the process of keeping tabs on a number of different events. Therefore, there are aspects of accounting that are useful in the everyday lives of almost everyone. In our culture, it is common practice to keep tabs on a wide range of dealings or behaviors. Accounting has a history that spans several centuries. Although the fundamentals are the same, technological advancements have led to significant changes in the way businesses manage their financial records. The purpose of this study is to provide an overview of the development of financial accounting and its impact on accounting standards. This study makes an effort to fill up a crucial knowledge gap by describing a conceptual framework for understanding financial accounting.